2021
DOI: 10.3390/nu13020456
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Omega-3 Fatty Acid Supplementation on Serum Adipocytokines, Lipid Profile and Biochemical Markers of Inflammation in Recreational Runners

Abstract: Background: The study aimed to evaluate the effects of a 3-week ω-3 PUFA supplementation on serum adipocytokines (i.e., adiponectin, leptin), neuregulin-4 (NRG4) and erythrocyte omega-3 (ω-3) fatty acid content, as well as the blood antioxidant defense capacity in non-elite endurance runners. Methods: Twenty-four runners were randomized into two groups: the supplemented group, who received omega free fatty acids extract containing 142 mg of EPA, 267 mg of DHA, 12 mg of vitamin E and 5 µg of vitamin D, each adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 85 publications
0
11
0
Order By: Relevance
“…The reduction in FGF21 is also in line with well-known anti-inflammatory functions of both EPA and DHA, since increased FGF21 levels have been associated with the presence of inflammatory chronic diseases, including metabolic syndrome [ 20 , 34 ]. Furthermore, FGF21 has been found to promote the metabolic events leading to type 2 diabetes mellitus, NAFLD, and obesity [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The reduction in FGF21 is also in line with well-known anti-inflammatory functions of both EPA and DHA, since increased FGF21 levels have been associated with the presence of inflammatory chronic diseases, including metabolic syndrome [ 20 , 34 ]. Furthermore, FGF21 has been found to promote the metabolic events leading to type 2 diabetes mellitus, NAFLD, and obesity [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 86%
“…The significant induction of the Omega-3 index detected in the grape group was associated with higher serum levels of adiponectin, a molecule known to have a key regulatory role in promoting fatty acids oxidation in the liver [ 34 , 35 ]. It has been reported that adiponectin release increases in response to EPA and DHA supplementation [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DHA reduced leptin mRNA expression in 3T3-L1 adipocytes [ 65 ]. In a study by Zebrowska et al, human subjects who received two doses of 267 mg of DHA for three weeks exhibited a significant decrease in circulating leptin concentration and an increase in adiponectin level, which was accompanied by a decrease in plasma TNF and oxidative stress markers and an improvement in lipid profile [ 66 ]. Consistent with prior research, our results revealed that 3T3L-1 mature adipocytes exposed to low oxygen tension (1% O 2 ) exhibited a substantial drop in adiponectin release [ 7 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…[83][84][85] Serum NRG4 increased significantly in response to a 3-week ω-3 polyunsaturated fatty acids dietary protocol. 86 Plasma levels of NRG4 were improved in three training protocols: high-intensity interval training (HIIT), circuit resistance training (CRT), and moderate intensity continuous training (MICT) compared with the control group. What is more, the increase was greater in HIIT and CRT compared with the MICT.…”
Section: Clinical Studiesmentioning
confidence: 99%